1768 Nuclear Transit Scintigraphy (NTS) Provides Objective Assessment of Gastrointestinal Transit in Children with Slow-Transit Constipation (STC). (October 2012) - Yik, YI; Cook, DJ; Veysey, DM; Tudball, CF; King, BS; Morris, KA; Cain, TM; Hutson, JM; Southwell, BR
Abstract : Background: /aims: Children with slow-transit constipation (STC) are resistant to medical treatment. We used a new treatment - transcutaneous electrical stimulation (TES) to treat STC children since 2005, with improved symptoms in most children. Home-based TES was available in 2008. We aimed to assess gastrointestinal transit (GIT) in STC children after medical treatment and home-based TES, with nuclear transit scintigraphy (NTS) as an objective assessment. We hypothesized that TES may alter gastrointestinal transit but not medical treatment in STC children. Methods: All STC children were diagnosed by NTS. STC children treated medically ("Control", n=29 - from NTS database) were compared with 45 STC children treated with home-based TES (1-hour dailyx6 months from 2009–2011). Gastrointestinal transit measured gastric emptying (t½) and colonic transit by geometric centre (GC) at 6, 24, 30 & 48 hours. The effects of treatments were measured by a repeat NTS. Pre- and post-treatment NTS data were analysed with paired t-test; p<0.05 considered significant. Symptoms assessments were based on bowel diary recorded. Ethics approval obtained (HREC30059A&30116A). Results: Control group has no improvement in symptoms with most STC children treated with home-based TES has improved symptoms. GC and GIT significantly improved in STC children treated with home-based TES (Table 1 ). Conclusions: We found symptoms and gastrointestinal transit improved in STC children with home-based TES but not with medical treatment. NTS provides objective assessment, which is important to confirm clinical status after treatments and helps to decide on further interventions.